2020
DOI: 10.1021/acs.jpcc.0c00713
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Water Molecule on Calcium Fluoride and Magnesium Fluoride Surfaces: A Combined Theoretical and Experimental Study

Abstract: The adsorption and dissociation of H2O molecule on various surfaces of MgF2 and CaF2 have been investigated theoretically by using a dispersion-corrected density functional theory based method. The calculated adsorption energy of H2O molecule on the low index CaF2(110) and CaF2(111) surfaces ranges from −0.20 to −0.50 eV, smaller than those on the low index MgF2(001) and MgF2(110) with values from −0.80 to −1.06 eV. The modeling shows that the dissociation of water molecule is possible on the high index CaF2(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…Obtaining such insights is very challenging, as is clear from the common mineral fluorite (i.e., calcium fluoride, CaF 2 ). There are numerous studies elaborating on the structure and dynamics of the fluorite‐water interface, its surface potential, streaming potential, and surface chemistry [5–17] . In 2004, Miller et al [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining such insights is very challenging, as is clear from the common mineral fluorite (i.e., calcium fluoride, CaF 2 ). There are numerous studies elaborating on the structure and dynamics of the fluorite‐water interface, its surface potential, streaming potential, and surface chemistry [5–17] . In 2004, Miller et al [7] .…”
Section: Introductionmentioning
confidence: 99%
“…The FT-IR spectra for both FL-CaF 2 and FL-CaF 2 -R are almost identical to those for CaF 2 nanoparticles reported in our previous work. 33 It is found that: (1) the adsorbed water molecules cannot be completely desorbed by the prolonged evacuation at low temperatures, implying that CaF 2 interacts with the adsorbed water molecules strongly; (2) the adsorbed water molecules on the fresh sample will be completely desorbed under vacuum at temperatures up to 573 K for 7 h, which is in good agreement with the observation by Barraclough and Hall 14 who claimed that the strongly adsorbed water molecules might be "trapped" on the specific surface of CaF 2 during the synthesis; and (3) after the fresh sample is outgassed at 573 K, the readsorbed water molecules on the CaF 2 surface can be completely desorbed under vacuum at 473 K for 3 h.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The disk-stacked MIM nanostructures are expected to have two LSP modes that generate electric fields outside the MIM nanostructures and inside the insulator layer, and are expected to independently respond to the changes in two phases: the surrounding medium and inside the insulator layer. In addition, by introducing MgF 2 , which is known to adsorb hydroxyl groups of water molecules [40,41] as the insulator layer, the MIM nanostructures are expected to respond to the hydroxyl group by the LSP mode, which generates electric fields inside the insulator layer. By combining the individual mode distribution and the adsorption characteristics of MgF 2 , the MIM nanostructures are expected to monitor the information of both the RI change in the solution and the changes within the MgF 2 layer (corresponding to the interaction of molecules in solution with MgF 2 ).…”
Section: Introductionmentioning
confidence: 99%